Photographers and research the role of research in contemporary photographic practice - Read, Shirley; Simmons, Mike (Routledge, an imprint of the Taylor and Francis Group, 2017)
"This ground-breaking book situates research at the heart of photographic practice, asking the key question: What does research mean for photographers? Illuminating the nature and scope of research and its practical application to photography, the book explores how research provides a critical framework to help develop awareness, extend subject knowledge, and inform the development of photographic work. The authors consider research as integral to the creative process and, through interviews with leading photographers, explore how photographers have embedded research strategies into their creative practice." -- Preliminary page 1.